Narrative Empathy and the Challenge of the Unrelatable - Keen, Suzanne (Bollettino Filosofico, 2022)
The essay explores the everyday aesthetic judgment embedded in “relatable” representations and takes on the challenge of the “unrelatable”. It advances the theorizing of narrative empathy by considering why some representations are judged “unrelatable”. The unrelatable fails at the first hurdle if it was crafted with the intention of evoking empathy (though not all narratives share that aim). If narratives are to galvanize feeling for distant others, nonhuman animals, the inanimate world and changing climate, and our descendants, then understanding what makes representations unrelatable matters. But if the response inheres primarily in readers, then forbearance from condemnation matters more. Keywords: Failed Empathy, Relatable, Storyworld, Strategic Narrative Empathy, Unrelatable